The adaptive immune response does not influence hantavirus disease or persistence in the Syrian hamster. Issue 2 (12th September 2013) - Prescott, Joseph; Safronetz, David; Haddock, Elaine; Robertson, Shelly; Scott, Dana; Feldmann, Heinz
Summary Pathogenic New World hantaviruses cause severe disease in humans characterized by a vascular leak syndrome, leading to pulmonary oedema and respiratory distress with case fatality rates approaching 40%. Hantaviruses infect microvascular endothelial cells without conspicuous cytopathic effects, indicating that destruction of the endothelium is not a mechanism of disease. In humans, high levels of inflammatory cytokines are present in the lungs of patients that succumb to infection. This, along with other observations, suggests that disease has an immunopathogenic component. Currently the only animal model available to study hantavirus disease is the Syrian hamster, where infection with Andes virus (ANDV), the primary agent of disease in South America, results in disease that closely mimics that seen in humans. Conversely, inoculation of hamsters with a passaged Sin Nombre virus (SNV), the virus responsible for most cases of disease in North America, results in persistent infection with high levels of viral replication. We found that ANDV elicited a stronger innate immune response, whereas SNV elicited a more robust adaptive response in the lung. Additionally, ANDV infection resulted in significant changes in the blood lymphocyte populations. To determine whether the adaptive immune response influences infection outcome, we depleted hamsters of CD4+ and CD8+ T cells before infection with hantaviruses. Depletion resulted in inhibition of virus‐specific antibody responses, although the pathogenesis and replication of these viruses were unaltered. These data show that neither hantavirus replication, nor pathogenesis caused by these viruses, is influenced by the adaptive immune response in the Syrian hamster.